Cutting edge: CD1d restriction and Th1/Th2/Th17 cytokine secretion by human V¿3 T cells. - O'REILLY, VINCENT; DOHERTY, DEREK (My University, 2013)
Human γδ T cells expressing the Vδ3 TCR make up a minor lymphocyte subset in blood but are enriched in liver and in patients with some chronic viral infections and leukemias. We analyzed the frequencies, phenotypes, restriction elements, and functions of fresh and expanded peripheral blood Vδ3 T cells. Vδ3 T cells accounted for ~0.2% of circulating T cells, included CD4(+), CD8(+), and CD4(-)CD8(-) subsets, and variably expressed CD56, CD161, HLA-DR, and NKG2D but neither NKG2A nor NKG2C. Vδ3 T cells were sorted and expanded by mitogen stimulation in the presence of IL-2. Expanded Vδ3 T cells recognized CD1d but not CD1a, CD1b, or CD1c. Upon activation, they killed CD1d(+) target cells, released Th1, Th2, and Th17 cytokines, and induced maturation of dendritic cells into APCs. Thus, Vδ3 T cells are glycolipid-reactive T cells with distinct Ag specificities but functional similarities to NKT cells.
PUBLISHED
Keywords: cytokine secretion; Immunology, Inflammation & Infection; International Development